2017
DOI: 10.1016/j.pharep.2017.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the calcium-sensing receptor influences blood glucose and insulin levels in rats

Abstract: We suggest that modulation of the CaR activity may participate in the mechanisms which mediate insulin secretion in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Experiments performed on pancreatic β-cells in vitro show that activation of calcium receptor by calcimimetic R-568 increases insulin secretion, which is due to enhanced release of Ca 2+ from intracellular storages and increased cytoplasmic Ca 2+ concentration (19). Our recently published in vivo experiments confirmed the hypothesis that modulation of CaR activity may also participate in the mechanisms that mediate insulin secretion since the administration of R-568, an agonist of CaR increased insulin level in rats whereas CaR antagonist, NPS2143, had the opposite effect (20). Furthermore, calcium channel blockade by verapamil may prevent changes in blood glucose and insulininduced by CaR activation in rats (21).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Experiments performed on pancreatic β-cells in vitro show that activation of calcium receptor by calcimimetic R-568 increases insulin secretion, which is due to enhanced release of Ca 2+ from intracellular storages and increased cytoplasmic Ca 2+ concentration (19). Our recently published in vivo experiments confirmed the hypothesis that modulation of CaR activity may also participate in the mechanisms that mediate insulin secretion since the administration of R-568, an agonist of CaR increased insulin level in rats whereas CaR antagonist, NPS2143, had the opposite effect (20). Furthermore, calcium channel blockade by verapamil may prevent changes in blood glucose and insulininduced by CaR activation in rats (21).…”
supporting
confidence: 52%
“…ing blood glucose concentrations. Furthermore, we indicated that inhibition of the CaR by calcilytic NPS2143 provoked the opposite effects (20). Used in our experiments diazoxide increases blood glucose concentration by inhibiting pancreatic insulin secretion.…”
mentioning
confidence: 65%
“…Marquis et al showed that NPS2143 had a good specificity with only a few additional targets like monoamine transporters [ 36 ], which may lead in minor side effects. It was recently tested for osteoporosis treatment and calcium hemeostasis related diseases [ 37 – 39 ], and in vivo has demonstrated a good biocompatibility [ 40 , 41 ]. Thus, RCC patients with bone metastases and increased CaSR expression might benefit from a therapy with antagonists like NPS2143, justifying further preclinical and clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by diabetes mellitus, which is characterized by hyperglycemia due to a deficiency of insulin. Recently, it was shown that CaSR is one of the factors that modulates insulin secretion [52]. The constant hyperglycemic condition upregulates the expression of CaSR in cardiac fibroblasts which eventually leads to an increase in the intracellular calcium levels and activation of autophagy and the Smurf2 ubiquitin proteasome which is highly involved in protein degradation [52].…”
Section: Heart Failurementioning
confidence: 99%